Evaluation of the applicability of the X-ray room technical passports in the medical facilities and approval of the X-ray department technical plans by the local radiological authorities - I. I. Berezin; S. S. Somov; К. V. Yakusheva (Радиационная гигиена)
The technical passport for the X-ray room in accordance with the current sanitary legislation is a mandatory document certifying the technical condition of X-ray diagnostic equipment, devices for developing, fixing and drying X-ray films, additional equipment and accessories for performing special types of X-ray diagnostics, means of protection against ionizing radiation of workplaces of the office staff and adjacent to the office of the premises and confirming the compliance of their characteristics with the normative and technical documentation and domestic standards. The purpose of this work was to assess the relevance and necessity of issuing a technical passport for the X-ray room and to coordinate the project of the X-ray room with the X-ray department in the light of the current sanitary legislation. Registration of a technical passport by organizations that have special permits for these types of work, and not only by the X-ray and radiological department, would increase the legal value of the technical passport. The information contained in the technical passport is duplicated in the rest of the documentation for the X-ray room, the requirements for which are enshrined in the sanitary legislation, which generally casts doubt on the need for a technical passport as a mandatory document.